How can low germination rates in Amazon chicory seeds be overcome? - Isabelle Caroline Bailosa do Rosário; Renata da Silva Arruda; Andressa de Oliveira Silva; Rafaelle Fazzi Gomes (Ciência Rural, 2024)
ABSTRACT: Eryngiumfoetidum exhibits low germination rates and heterogeneous seed maturation. Thus, in order to reduce problems during seedling production, a number of treatments can be used. The aim of this study was to assess the physiological quality of Amazon chicory seeds submitted to water immersion treatments. Two experiments were conducted, under controlled temperature (25 ºC) and nursery conditions, with six treatments (0, 12, 24, 36 and 48 hours) in each. A completely randomized design was used in the controlled condition and random blocks in the nursery. The following were assessed: germination/emergence speed index (GSI/ESI), mean germination/emergence time (MGT/MET), germination/emergence percentage, normal seedling development, fresh weight and dry weight. The data were submitted to linear and second-order polynomial regression analysis in the R statistical program. Under controlled conditions, Maximum GSI was 4.65 after 18.03 hours of immersion, and for MGT, 12 h of immersion provided a shorter average time (13.76 days) and obtained 39.26% of germinated seeds after 26.27 h of immersion, as well as 19.34% of normal seedlings in 27.97 h. In the nursery, a lower MET was observed after 48 h and mean fresh and dry weight were higher after 12 h (18.47 and 1.44 g, respectively). Thus, water immersion for 12 hours resulted in a shorter germination time and higher fresh and dry weight, and the treatment may have helped reactivate embryo metabolism and growth.